Ethnobotany of Medicinal Plants for Internal Diseases in the Village Community of Fatulotu of Lasiolat District of Belu Regency - Mario Justinianus Santrum (Haumeni Journal of Education, 2021)
ABSTRACT: this research aims to study kinds of plants that have medicinal properties, traditional ways to use the plants as traditional medicinal ingredients, and traditional rituals performed in curing internal diseases in the Fatulotu village community of Lasiolat district of Belu regency. This research was carried out between October and November 2013 in the Fatulotu village community of Lasiolat district of Belu regency. The method of this research is field observation. Data were collected by survey and interview tecnique. Survey tecnique is used to obtain data about the kinds of plants that have medicinal properties. While, interview tecnique is used to obtain data about the rituals performed in healing internal diseases. The results showed that there were 22 species of plants that have medicinal properties that could be group into 16 plant families and could cure 16 kinds of internal diseases. The ways of processing plants to be used as traditional medicine ingredients varies depending on the types of diseases. Shaman is accompanied by several villagers performing rituals when taking natural materials. The rituals are carried out in the form of certain treatments on the plants and the recitation of spells by shaman.